Impact of Formulation Composition on the Antioxidant Activity of a Peel-Off Gel Mask Containing Peronema canescens Jack Leaf Powder - Henni Rosaini; Yeni Novita Sari; Khoirunnisa Khoirunnisa; Wahyu Margi Sidoretno (LPPM Universitas Abdurrab, 2025)
Peel-off gel masks are cosmetic gel preparations that are practical and convenient for facial application, as they form a thin film upon drying and can be removed without rinsing. This study aimed to evaluate the effect of formulation composition on the antioxidant activity of a peel-off gel mask containing Peronema canescens Jack leaf powder. The peel-off gel mask was formulated into three formulations: F0 as a control formulation without active ingredients, F1 containing 20% leaf powder, and F2 containing 25% leaf powder. Antioxidant activity was evaluated using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging method. Prior to formulation, Peronema canescens Jack leaf powder exhibited very strong antioxidant activity with an IC₅₀ value of 20.6678 µg/mL. The formulated peel-off gel masks demonstrated antioxidant activity, with F1 showing active antioxidant properties (IC₅₀ = 54.5120 µg/mL) and F2 exhibiting very strong antioxidant activity (IC₅₀ = 48.0615 µg/mL). The results indicate that variations in formulation composition influence the antioxidant activity of the peel-off gel mask. Although a decrease in antioxidant activity was observed after formulation compared to the leaf powder alone, increasing the concentration of the active ingredient enhanced the antioxidant activity of the final product. In conclusion, the formulation composition plays a significant role in determining the antioxidant activity of peel-off gel masks containing Peronema canescens Jack leaf powder